Evaluation of Self-Healing Efficiency of Reinforced Concrete Beams with Calcium Nitrate Microcapsules. Issue 1 (2017) - Bonilla, Luis; Hassan, Marwa; Noorvand, Hassan; Rupnow, Tyson; Okeil, Ayman
The self-healing efficiency of cementitious materials was improved by developing several strategies to provide and deliver the products (healing agents) needed for cracks to self-repair. This study evaluated the self-healing efficiency of microcapsules filled with calcium nitrate in reinforced and unreinforced concrete beams. The structural behavior and healing efficiency were evaluated by measuring and then comparing the initial stiffness, peak strength, and deformation with posthealing measurements. Furthermore, as part of this study, crack monitoring was conducted to evaluate crack healing over time. Then characterization analysis was carried out with energy dispersive X-ray spectroscopy to quantify the healing components in the cracked areas. Results showed that the air content in samples containing microcapsules was two times higher than that in the control samples. Furthermore, addition of microcapsules lowered the flexural strength of concrete beams compared with that of the control samples. A positive stiffness recovery was recorded for all groups, with and without microcapsules or steel. Control samples showed the lowest stiffness recovery; however, the use of steel with microcapsules presented a superior healing efficiency and improved stiffness recovery significantly by 38%. Results from image analysis showed that crack widths did not completely heal for the control samples, while using microcapsules allowed the cracked widths to heal more efficiently. The best observed performance was for the microcapsules–steel group, which yielded 100% healing of the cracks.